Outcomes between superior capsular reconstruction and graft bridging with allogenic decellularized dermis graft for massive rotator cuff tear - Ching-Di Chang; Chun-Jui Weng; Wen-Yi Chou; Chung-Cheng Huang; Wei-Xiong Lim; Jih-Yang Ko; Jai-Hong Cheng (Medicine, 2026)
The utilization of allogenic decellularized dermis graft is an emerging option in the treatment of massive tears in the rotator cuff. Our purpose is to evaluate patients undergoing superior capsular reconstruction (SCR) and the graft bridging (GB) technique using allogenic dermis graft. In addition, we aim to identify the prognostic factors that contribute to graft failure. This case–control study investigates the clinical and radiologic evaluations of patients with irreparable massive rotator cuff tear before and 12 months after the allogenic decellularized dermis graft. Our clinical evaluations include assessments of the intensity of the visual analogue scale and Constant score, both prior to and 12 months following the surgical intervention. Radiographic analysis includes Hamada classification, acromiohumeral interval, coracohumeral distance, graft integrity, and Goutallier grade on plain radiography or magnetic resonance imaging, both taken before and 12 months after the surgical intervention. A total of 24 patients were enrolled in the study, with 14 patients undergoing graft bridging procedures and the remaining patients receiving SCR. After the surgery, all patients experienced a significant improvement in various measures, including the visual analog scale, Constant score, and coracohumeral distance. The follow-up magnetic resonance imaging showed that 62.5% of the patients had a healing graft, while 37.5% had a failed graft. Moreover, patients in the graft failure group had lower visual analog scale scores, decreased acromiohumeral interval, late-stage Goutallier muscle atrophy, and higher Hamada classification compared with the graft healing group. The use of decellularized allogeneic dermis grafts in the SCR/graft bridging technique led to improvements in pain and functional outcomes. Preoperative prognostic factors for graft failure included lower preoperative pain, decreased acromiohumeral interval, Goutallier muscle atrophy (grade 3 or higher), and advanced cuff tear arthropathy (Hamada grade 3 or higher).